PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME UNTUK MATERI KUBUS, BALOK, PRISMA DAN LIMAS PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMPN 33 PADANG - Dhorys Ratna Anggelia, Dhorys Ratna Anggelia; Harisman, Yulyanti; Melisa, M.Pd., Melisa (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ This research wasmotivated because of the students difficulties in constructing the concepts and lack of the learning sources that facilitate the students to learn independently. To overcome these problems, the constructivis based module was developed for cube, block, prism and pyramid material. This study aimed to develop a valid module based constructivism in SMPN 33 Padang. This type of research was a development research. This study used model of 4-D which consisted of 4 phases: definition, design, development andÂ disseminate phases. This study was only done in 3 phases, the definition, design and development phase. The development phase was done to see the validity. The needs analysis was done by the teacher and students interview, analysis syllabus and reference books that already have existed. The result showed that the module which had been developed based constructivism was very valid according to the mathematicians and linguists.